IMPROVING STUDENTS ACHIEVEMENT IN WRITING NARRATIVE TEXT BY APPLYING SPORE STRATEGY - Putri Febrini Sianturi (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2014)
This study aims to discover the improvement of the students’ achievement in writing narrative text by applying Spore Strategy. The objective of this study is to find out whether the Spore strategy can improve students’ achievement in writing narrative text or not. This study was conducted by using classroom action research. The subject of the research was class XI IPA 2 of SMA Negeri 6 Medan which consists of 34 students. This study applied quantitative and qualitative data. The data of this study were obtained quantitatively through writing test which show that the students score kept improving in every test and qualitatively based on diary notes, observation sheet and interview sheet which show that teaching learning process ran well, the students were active, enthusiastic, and interested in writing. In the first test, the mean score was 56.8. In the second test, the mean score was 67.2, and in the third test the mean score was 81.2.The research findings indicated that Spore Strategy significantly improved students’ achievement in writing narrative text.   Keywords: Writing, Spore Strategy, Test, Data, Classroom Action Research.